Sustainable Development Conception for International Governance Towards the Agenda 2030: Analysis of Historical Events - Faustino, Annemara; Junior, Oklinger Mantovaneli [UNESP]; Barbosa, Valeska Cristina (Historia Ambiental Latinoamericana y Caribena - HALAC, 2024)
Sustainable development has gained prominence on global agendas, aiming to reconcile socioeconomic advancement with environmental sustainability preservation. International governance represents a pathway to achieving feasible sustainable management, crucial in defining and implementing strategies to reach sustainability by 2030 Agenda. This research proposes an analysis of related historical events influencing the conception of sustainable management from 19th to 21st-century international governance. Through a systematic literature review, analysis of relevant documents, and international events, identifying historical milestones significantly impacting these concepts. Highlighted are international conferences, reports, and agreements contributing to the construction of a global sustainability agenda, such as the Stockholm Conference in 1972, Brundtland Report in 1987, Earth Summit in Rio de Janeiro in 1992, and United Nations (UN) Agendas leading up to the Sustainable Development Goals (SDGs). Commonly, these historical milestones aimed to enable comprehensive understanding of international governance for sustainable management, providing a broad view of conceptual and practical foundations related to these themes. Moreover, they allow reflection on challenges and opportunities in the context of sustainable development, relating to the conception and identifying strategies for implementing the 2030 Agenda.
Concepção de Desenvolvimento Sustentável para a Governança Internacional: Análise dos Eventos Históricos até a Agenda 2030
Keywords: 2030 agenda; international governance; sustainable development; sustainable management